PENGARUH KETERLIBATAN KERJA DAN FLEXIBLE WORKING ARRANGEMENT TERHADAP WORK LIFE BALANCE PADA KARYAWAN PT DHASATRA MONEY TRANSFER - Aji Candra; Uswatun Chasanah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the effect of Job Involvement and Flexible Working Arrangement on Work Life Balance of PT Dhasatra Money Transfer employees. This type of research is descriptive quantitative with data analysis methods consisting of descriptive statistical analysis, classical assumption test, regression analysis, correlation coefficient test, hypothesis test, and determination coefficient test with SPSS version 25 program. The data sources used in this study are secondary data sources. The results of this study indicate that the Job Involvement variable has a calculated t value> t table (2.340> 2.0395) with a significance value of 0.026 <0.05, meaning that there is a positive and significant partial influence between Job Involvement and Work Life Balance. The Flexible Working Arrangement variable has a calculated t value> t table (2.521> 2.0395) and a significance value of 0.017 <0.05, meaning that there is a positive and significant partial influence between Flexible Working Arrangement and Work Life Balance. The results of the F test show that the calculated f value is > f table (8.128 > 0.05) so that H03 is rejected and Ha3 is accepted, meaning that there is a simultaneous influence between Work Involvement and Flexible Working Arrangement on Work Life Balance. Keywords: Work Involvement, Flexible Working Arrangement, Work Life Balance